ENGLISH LANGUAGE EDUCATION AND CHARACTER BUILDING FOR ELEMENTARY STUDENT THROUGH STORYTELLING BASED ON UPANISAD STORIES - Ayu Nikki Avalokitesvari, Ni Nyoman (Yavana Bhasha : Journal of English Language Education, 2018)
This article aimed to describe the role of storytelling based on Upanishad stories on English language education and character building for elementary student. Storytelling is the original form of teaching and has the potential of fostering emotional intelligence and help the child gain insight into human behavior. Storytelling also promotes language learning by enriching learnersâ€™ vocabulary and acquiring new language structures. Moreover, storytelling can provide a motivating and low anxiety context for language learning. There are several stories derived from Purana and Upanishad. One of those story from Upanishad that can be used to build a strong and good character as well as training them to learn English for kids in elementary school is the story of Nachiketa.Â Keywords: English Language Education, character building, Storytelling, Upanishad Stories